Manajemen Kinerja Berbasis Pohon Sasaran Kerja dan Inovasi Berlevel - Adi Asmariadi Budi (Inovasi Pembangunan : Jurnal Kelitbangan, 2016)
Performance Allowance System which applied in Lampung Province has an objective to increase civil servant performance. The mechanism of this system is giving allowance beside primary salary to civil servant where the amount is based on attendance and job list and function. That system has been applied since January 2015. The problem is that system does not give a significant performance increasing. It is shown from public opinion from local newspaper which has title article “Performance Allowance Create Attendance Based Employee”. This research objectives were to provide a better understanding about management which can increase civil servant performance and to design performance assesment based on objective tree with apply innovation at work. Research method using review of literatures and theory. Control system theory in engineering is applied to analyze performance management system. Application of that theory can create a new analysis method which called performace management control system. Based on this analysis, the results showed that the problem on existing performance allowance system is on objective fullfilment method which not oriented to objective result. Analysis result through theory review found that management system design based on objective tree to increase civil servant objective result. Building innovation at work for civil servant is done by innovation with level system, which is applied in game addiction concept.